Essential commodities prices, availability, and market actors’ perceptions: September 2025 - Siddig, Khalid; Rakhy, Tarig; Abushama, Hala; Mohamed, Shima; Nigus, Halefom Yigzaw (International Food Policy Research Institute, 2025)
In September 2025, Sudan’s markets showed relative stability despite conflict, inflation, and weather related disruptions. Cereal and vegetable prices remained broadly stable, while meat, oilseeds, and fuel saw moderate fluctuations. Availability of most essential goods improved slightly, though Darfur states continued to record the highest prices. The parallel exchange rate rose to about 3,100 SDG/USD, widening the gap with the official rate. Traders cited transport costs, heavy rains, and checkpoint fees as key drivers of higher prices, though logistical challenges eased from August. Liquidity and infrastructure conditions improved: 71 percent of merchants reported no cash short ages and 93 percent faced no storage or power issues. However, security risks persisted in Darfur and Kordofan, affecting trade safety. Profit margins remained mostly stable, while tax compliance declined, especially at the federal level. Despite ongoing challenges, merchants remain resilient—two-thirds plan to maintain current trade levels, and nearly one-fifth aim to expand, reflecting cautious optimism amid uncertainty.